Vaccines on time: Exploring determinants of delaying child vaccination in states of India - Pritu Dhalaria; Gopal Krishna Soni; Ajeet Kumar Singh; Amrita Kumari; Apurva Rastogi; Ayushi Agarwal; Divya Prakash; Prem Singh (Elsevier, 2022)
Aim: Timely vaccination is essential to achieve full potential of the vaccination especially in child population. Despite of success in increasing the coverage in India's universal immunization programme (UIP), timely vaccination remains a challenge. This study aims to understand the key socioeconomic correlates of vaccination delay and guide by charting the future course of action. Subject & methods: This study was a part of the review conducted in four states namely Madhya Pradesh, Rajasthan, Assam and Haryana to understand the equity issues in immunization. It was a cross-sectional study where 293 mothers of children aged 12-35 months were interviewed using semi-structured questionnaire. Association of delay in immunization and co-variates were examined through multilevel Poisson regression framework. Results: Timely vaccination was poor for most of the antigens except Measles. Only 52.6% of children had BCG on time and very few for Pentavalent doses as per the scheduled time (Penta-1: 3.4%, Penta-2: 1.4% and Penta-3: none). Whereas, measles showed better coverage (75%) for timely vaccination as compared to other basic antigens. About 72.7% received their basic vaccination in first year of life. Religion and mother's education were found to be associated with delay in all vaccination as per the schedule (at Birth, 6 weeks, 10 weeks, 14 weeks and 9-12 month). Conclusion: Timeliness of vaccination definitely requires attention to avoid increased risk of infection among children and avoid epidemics and outbreaks. There is a need to increase attention towards urban areas and improve the timeliness of vaccination and utilise the complete potential of the Universal Immunisation Programme (UIP).